Bronchoscopy as a Useful Examination for Determining Surgical Treatment Indications in Refractory Mycobacterium avium Complex Lung Disease Patients with Bilateral Lesions - Tabata, Erina (Intern Med, 2018)
We herein report three cases of refractory Mycobacterium avium complex (MAC) disease successfully treated surgically despite the MAC lesions being present bilaterally. Of note, although two patients did not present with any respiratory symptom, bronchoscopy clearly revealed a major excretory lesion with a large amount of purulent sputum in all patients. Because an excretory lesion was localized, surgical resection was performed, and the mycobacterial sputum smear became negative in all patients. Bronchoscopy may be a useful examination for detecting major excretory lesions with purulent sputum, which can disseminate to other lobes, and for determining the surgical indications of refractory MAC patients, regardless of the presence of respiratory symptoms.